Effects of different aberrations in the CRLF2 gene on the biological characteristics and drug sensitivities of Nalm6 cells. (4th December 2020) - Gu, Min; Jia, Yannan; Xu, Meizhen; Feng, Juan; Tian, Zheng; Ma, Xiaotong; Wang, Min; Wang, Jianxiang; Xu, Yingxi; Rao, Qing; Hao, Liangchun; Mi, Yingchang; et al.
Abstract: Introduction: To investigate the effects and mechanism of action of upregulated CRLF2 expression resulting from different aberrations in the CRLF2 gene ( CRLF2, CRLF2  +  IK6, P2RY8 ‐ CRLF2 and CRLF2 F232C) in the B cell ALL cell line Nalm6. Methods: Cell proliferation was measured using cell counting kit‐8. Transcriptome sequencing technology (RNA‐seq) was used to compare changes in gene expression resulting from different aberrations in CRLF2 . High‐throughput drug sensitivity testing was used to determine the drug sensitivity of cells. Results: All four aberrations in CRLF2 upregulated CRLF2 expression and promoted the proliferation of Nalm6 cells. The RNA‐seq results showed the upregulation of genes in the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway and the downregulation of genes in the cell cycle pathway in the CRLF2 F232C‐overexpressing cells. Western blotting showed that the expression of p‐STAT5 protein was significantly higher in the CRLF2 F232C‐overexpressing cells. Cells with aberrations in CRLF2 were more resistant to cyclophosphamide and drugs commonly used during treatment than cells in the vector group. The half‐maximal inhibitory concentration (IC50 or GI50 ) of dexamethasone was significantly higher in the CRLF2 F232C‐overexpressing cell line. Conclusions: The overexpression of CRLF2, CRLF2  +  IK6, P2RY8 ‐ CRLF2 and CRLF2 F232C promotes the proliferation of Nalm6 cells, activates the JAK/STAT signalling pathway and leads to a reduction in sensitivity towards various chemotherapeutic drugs.